PENJATUHAN PIDANA PENJARA KEPADA ANAK DI BAWAH UMUR YANG MEMBANTU TINDAK PIDANA PEMBUNUHAN BERENCANA (Studi Putusan Nomor 5/Pid.Sus.Anak/2014/PN.Siak) - Fransiskus Friska Buulolo (Jurnal Panah Hukum, 2023)
As for the background of the problem in this study, namely that minors were charged, prosecuted, and sentenced to commit premeditated murder as stipulated in Article 340 of the Criminal Code, while children did not know they were involved in the process of the intended act, where the child was only invited by the two other actors to fishing. The perpetrator's mistake did not report to the authorities or to the perpetrator's parents. Based on this background, the researcher formulates a research problem, namely how to impose prison sentences on minors who assist in the crime of premeditated murder. This study aims to find out and understand how imprisonment for minors assists in the crime of premeditated murder. The type of research used is normative legal research using secondary data. In the research findings it is known that the perpetrator was charged and prosecuted under Article 340 of the Criminal Code with a penalty of 9 years in prison. After the verification process in court, the panel of judges sentenced the perpetrator to 10 years in prison. Based on the research findings and discussion, the researcher can conclude that the judge punished the perpetrator for violating the provisions in Article 340 of the Criminal Code with a prison sentence of 10 years. The results of the analysis of the decision used, the researcher found irregularities in imposing a sentence on the perpetrator, namely the condition of the perpetrator in the case was not classified as an act of premeditated murder and/or participating in the criminal act, because he was only invited to fish by other actors without knowing the goals and intentions of other perpetrators. The perpetrator's mistake was only because he did not report the criminal act to the authorities, but the panel of judges did not consider the psychological factors of the perpetrator who was still underage. The suggestions for this research are that in examining and adjudicating children who are in conflict with the law, they should not only focus on the application of applicable law, but also consider juridical, non-juridical and child psychology in order to provide certainty about the application of the law to minors